Prove del Servizio Nazionale di valutazione e apprendimento della matematica: migliorare le performance della scuola primaria a partire dai risultati - Capperucci, Davide (Studi sulla Formazione/Open Journal of Education, 2017)
This paper investigates to what extent the educational system and school results can be used to promote self-assessment processes designed to improve pupils’ performances. It present the design, structure and frameworks used in the National Evaluation Service mathematics tests for primary school developed by INVALSI. The objective of this study is to highlight the strengths and weaknesses related to data processing and reporting, so as to increase the validity and reliability of the assessment procedures and tests. The results of this evidence-based research can be used by schools for formative assessment and to redefine the effectiveness of their teaching practices.